Characterization of the complete chloroplast genome of the Qinghai-Tibet Plateau endemic Pomatosace filicula. Issue 1 (2nd January 2019) - Wu, Lei; Du, Zheng; Hu, Quanjun
Abstract: Pomatosace filicula (Primulaceae) is an alpine biennial endemic to the Qinghai-Tibet Plateau, which is regarded as a kind of traditional Tibetan medicine. We assembled the whole chloroplast genome sequence of this endangered species based on Illumina pair-end sequencing data. The complete chloroplast genome was estimated to be 151, 277 bp in length, comprising a large single copy region of 82, 039 bp and a small single copy region of 23, 848 bp, separated by a pair of 22, 695 bp inverted repeat regions. The genome contained 121 genes, including 83 protein-coding genes (74 PCG species), 29 tRNA genes (24 tRNA species), and eight ribosomal RNA genes (four rRNA species). The overall AT content of P. filicula chloroplast genome is estimated to be 62.59%. This genetic resource will facilitate further conservation genetic studies of P. filicula based on designing new chloroplast DNA markers.